The Regionalisation of Judicial Review: Constitutional Authority, Access to Justice and Specialisation of Legal Services in Public Law. Issue 2 (1st March 2013) - Nason, Sarah; Sunkin, Maurice
<x xml:space="preserve">Abstract</x> Since April 2009 judicial reviews may be dealt with at regional centres and in Cardiff. This change significantly relaxed the hitherto highly centralised system of judicial review in England and Wales. The main aims were to improve access to public law redress by enabling cases to be listed and heard at the most appropriate regional location. Despite recognition of the need to improve regional access, fears exist that this reform will threaten the standing and authority of judicial review in this jurisdiction; that it will contribute to a fragmentation of judicial review and, in the regions, reduce the quality of public law adjudication, legal advice and representation. Drawing on an empirical study on the regional use of judicial review, this paper assesses these matters and considers the early effects of regionalisation on access to judicial review and the development of regional markets for legal services in public law.